Comparative Study on Cytotoxicity Endodontic Irrigants with & Without Silver Nanoparticle - Rushikesh. R Mahaparale, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Irrigation is the key part of successful RCT as the impact of irrigation on smear layer has shown a lot of attention in endodontics. Aim: To determine & assess by comparing the cytotoxicity of EI combined with & without Ag-NP. Material & method: Samples were assesed in 9 different groups after conducting a certain procedure which includes NS, NaOCl , AgNPs ,CHX, OTC &TCS. Result: We have found that statistically significant association seen all the groups. Conclusion: CTC of substances might be somewhat different when tested using various methods.